Leaderpreneruship: Integration Between Enterpreneruship and Leadership in Strengthening the Tourism Economy in Ilomata Village, Bilato District, Gorontalo Regency - Danial, Haris; Bay, Indri Wirahmi; Dako, Rahman Taufiqriyanto; Pakaya, Usman (Jurnal Pengabdian Sosial, 2024)
Ilomata Village is one of the villages in Bilato District, which is one of the centers of entrepreneurial activity in the region. Unfortunately, the lack of attention from the community and business actors, as well as leadership in upholding the tourism concept, is an obstacle to improving the tourism economy in the village. The ability to market tourism and businesses that are icons of the village is one of the biggest obstacles in the village. Moreover, the problem of English being a supporting system for improving the village economy requires intervention in regional development efforts. The MBKM "Building a Village" program aims to empower the community through Bilingual-based Entrepreneurship and Leadership Integration to Strengthen the Tourism Economy in Ilomata Village, Bilato District, Gorontalo Regency. This program is implemented through education and training, mentoring, service and coaching methods which are expected to be sustainable through awareness of related parties, especially the government and village parties, in paying attention to tourist destinations that have the potential to improve the community's economy.